International criminal law: Between law and politics - Jovašević Dragan (Međunarodni Problemi)
Crimes against international law are committed by violating the rules of international humanitarian law during wars or armed conflicts. The perpetrators of these crimes are under the jurisdiction of international criminal courts (military or civil, permanent or ad hoc). The process of the commission of crimes against international law may comprise several different phases or stadiums. Moreover, such criminal offences rarely appear as the results of only one person’s activities. On the contrary, in numerous cases of these criminal offences, accomplice appears as a form of collective participation of several persons in the commission of one or more crimes against international law. All these facts represent grounds for the specific type of criminal responsibility of the perpetrators of crimes against international law. It is a object of regulation international criminal law about whose characteristics converse this article.